2017
DOI: 10.4172/2155-6105.1000346
|View full text |Cite
|
Sign up to set email alerts
|

Ketamine Role in Schizoaffective Disorder Depressive Type

Abstract: Ketamine use for patients with severe treatment-resistant depression continues to be an area of interest due to the relatively limited number of treatment options for those patients. Although its use as a treatment option for patients with schizophrenia and schizoaffective disorder may seem counterintuitive, in this case report, we explore the efficacy of ketamine for depressive episodes in schizoaffective disorder. This patient who carried a diagnosis of schizoaffective disorder was given 300 mg of intramuscu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…This case discusses a patient in whom ketamine treatment safely improved the depressive symptoms of the disorder on a more long term basis. Although ketamine has yet to be used exclusively to treat the long term psychotic symptoms of this disorder, an alternate study showed that ketamine improved depressive symptoms from a 21 to a 4 on the Hamilton Rating Scale for Depression (HAM-D) over a four day hospitalization with a 300 mg ketamine treatment [2].…”
Section: Introductionmentioning
confidence: 99%
“…This case discusses a patient in whom ketamine treatment safely improved the depressive symptoms of the disorder on a more long term basis. Although ketamine has yet to be used exclusively to treat the long term psychotic symptoms of this disorder, an alternate study showed that ketamine improved depressive symptoms from a 21 to a 4 on the Hamilton Rating Scale for Depression (HAM-D) over a four day hospitalization with a 300 mg ketamine treatment [2].…”
Section: Introductionmentioning
confidence: 99%